2010
DOI: 10.1111/j.1442-200x.2009.02967.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose vasopressin infusion therapy for refractory hypotension in ELBW infants

Abstract: Low-dose AVP therapy should be considered as rescue therapy when high-dose catecholamine therapy and/or steroid administration do not produce sufficient increase in the blood pressure. Further investigations are required to prove the efficacy and safety of AVP infusion therapy in preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 32 publications
2
33
1
2
Order By: Relevance
“…In this group 4 patients were in the transitional circulation period. All patients responded with increase in BP and urine output but mortality was 100% [101]. The reason underlying rare use of AVP in the neonatal population may be the fear of potential untoward effects of the medication characterized with peripheral ischemia due to severe vasoconstriction, decreased mesenteric or renal blood flow, hyponatremia, elevated liver enzymes and effects on platelet aggregation which have been reported in adults [102].…”
Section: Evidence and Pd Effectsmentioning
confidence: 94%
“…In this group 4 patients were in the transitional circulation period. All patients responded with increase in BP and urine output but mortality was 100% [101]. The reason underlying rare use of AVP in the neonatal population may be the fear of potential untoward effects of the medication characterized with peripheral ischemia due to severe vasoconstriction, decreased mesenteric or renal blood flow, hyponatremia, elevated liver enzymes and effects on platelet aggregation which have been reported in adults [102].…”
Section: Evidence and Pd Effectsmentioning
confidence: 94%
“…We did not use noradrenaline, which strongly increases cardiac muscle contractions, because the patients in this study had hypertrophic cardiac muscle due to twin-totwin transfusion syndrome (TTTS) or treatment with adrenocorticosteroids and were assumed to have a low cardiac output because of hypertrophic cardiomyopathy. The dose of AVP infusion was at the discretion of the attending neonatologist, with reference to Ikegami et al who used AVP at a dose of 1-10 mU/kg/min (Ikegami et al 2010). The patient heart rate, BP, urine volume, RI, and blood flow velocity pattern in the renal artery were statistically compared before and after AVP administration.…”
Section: Methodsmentioning
confidence: 99%
“…The causes of hypotension in ELBW infants are diverse, including septic shock, gastrointestinal perforation, intraventricular hemorrhage, and adrenal insufficiency. Recent studies have reported that arginine vasopressin (AVP) infusion is an effective treatment for ELBW patients exhibiting hypotension refractory to treatment with catecholamines and adrenocorticosteroids (Meyer et al 2006;Bidegain et al 2010;Ikegami et al 2010). Treatment with AVP was originally shown to increase blood pressure (BP) in hypotensive adult patients with septic shock (Landry et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…the decision to initiate AVP/TP was made only in children who were refractory to fluid resuscitation and conventional inotropes and all children were considered to be in an extreme state of shock). The age ranged from extremely low birthweight infants [29,34] up to a 19-year-old patient. Sixteen articles were descriptive case series [14, 17, 18, 22, 24, 26-29, 34-38, 40, 41], 10 reports were case reports [12, 13, 15, 16, 19-21, 25, 30, 33], three were clinical evaluation studies [23,32,39], one study was a non-blind randomised control trial [11] and one was a multicentre double-blind randomised control trial [31].…”
Section: Studies and Patients Includedmentioning
confidence: 99%
“…In most reports, AVP and TP were exclusively used as a rescue therapy in severe forms of septic, cardiogenic, anaphylactic and hypotensive shock that was not responsive to catecholamines. Twelve reports were confined solely to septic patients [11][12][13][14][15][16][17][18][19][20][21][22], 6 reports were solely on patients with low cardiac output and/or concomitant severe vasodilation following cardiac surgery in some patients [23][24][25][26][27][28], 10 included a heterogenous population (septic shock, cardio-circulatory failure secondary to congenital heart disease, haemorrhagic and anaphylactic) [29][30][31][32][33][34][35][36][37][38] (for more details regarding septic vs. cardiac shock please see below). TP and AVP were used for cardiopulmonary resuscitation in three articles [39][40][41].…”
Section: Studies and Patients Includedmentioning
confidence: 99%